Feminist moments : reading feminist texts - Bruce, Susan, 1960-; Smits, Katherine (New York : Bloomsbury Academic, 2015)
'The challenges presented by feminism to traditional understandings of representation, normative values, power relations and the political are not simply the product of late-20th century thinking. Feminist Moments, in examining some of the pivotal texts in the history of feminist thought, demonstrates that these challenges emerge from a long and varied history of feminist writing. The volume brings together texts from literary and analytical works written by women and men, and from inside and outside the Western tradition, including Mary Wortley Montagu, Anna Wheeler and William Thompson, Nazira Zeineddine, Betty Friedan, Andrea Dworkin and Luisa Valenzuela. The volume is unique in offering close readings of key passages from the selected texts, making it ideal for classroom use; its original essays, all authored by specialists, will also be of interest to more advanced scholars. In juxtaposing and analysing a wide range of texts which despite their significance are rarely discussed together, Feminist Moments provides a fascinating historical narrative of feminist thought which will be highly valuable to students and scholars of the history of political thought, political philosophy and gender and literary studies'--
'Feminism has fundamentally changed the ways in which we think about politics - in terms of representation, normative values, power relations and our very understanding of what the political means. These questions are not simply the product of late 20th century thinking. They build on a long and varied historical traditional of feminist writing. This volume examines some of the pivotal texts in the history of feminist thought, selected from both literary and analytical works, from the work of women and men, and from inside and outside the Western tradition. It is unique in offering close readings of short and highly pertinent passages in the texts selected, making it ideal for classroom use and for those progressing from texts offering a more general overview. Essays are included on a range of authors who have made significant contributions to feminist discourse but are not frequently anthologised, including Rachel Speght, Mary Wortley Montagu, Anna Wheeler and William Thompson, Maria Stewart and Roquia Sakhawat Hussain'--
Machine generated contents note: -- Introduction -- 1. Christine de Pizan: The Book of the City of Ladies (1405) Nadia Margolis -- 2. Rachel Speght: A Mouzell for Melastomus (1617) Helen Wilcox -- 3. Anne Bradstreet: Poems (1670s) Susan Bruce -- 4. Mary Astell: A Serious Proposal to the Ladies, for the Advancement of their True and Greatest Interest (1694) Patricia Springborg -- 5. Mary Wortley Montagu: The Turkish Embassy Letters (1763) Vicki Spencer -- 6. Olympe de Gouges Declaration of the Rights of Women (1791) Joe Zizek -- 7. Mary Wollstonecraft: A Vindication of the Rights of Women (1792) Barbara Taylor -- 8. Anna Wheeler and William Thompson Appeal on Behalf of Women (1825) Jim Jose -- 9. Maria Stewart: a selection from her published lectures (early 1830s) Valerie Cooper -- 10. Charlotte Bronte: Jane Eyre (1847) Alexandra Lewis -- 11. John Stuart Mill: The Subjection of Women (1869) Katherine Smits -- 12. Charlotte Perkins Gilman: The Yellow Wallpaper (1892) Shirley Samuels -- 13. Clara Zetkin: a selection from one of her published speeches (1890s -- 1930) Marilyn Boxer -- 14. RoquiaSakhawatHussain: Sultana's Dream (1905) Maitrayee Chaudhuri -- 15. Nazira Zain al'Din: Veiling and Unveiling (1928) Miriam Cook -- 16. Virginia Woolf: A Room of One's Own (1929) Amber Regis -- 17. Sylvia Pankhurst: The Suffragette Movement (1931) Karen Hunt -- 18. Zora Neale Hurston: Their Eyes were Watching God (1937) Glenda Carpio -- 19. Simone de Beauvoir: The Second Sex (1949) Nancy Bauer -- 20. Adrienne Rich: Poems (1970s) Sabine Sielke -- 21 Andrea Dworkin: Pornography: Men Possessing Women (1981) Helen Pringle -- 22. Luisa Valenzuela: Short Story to be advised (1999 to date) Valeria Wagner -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: Feminism -- History